Ethnographic Research in the Changing Context: Some Reflections on Ethical Issues and Dilemma - Sapkota, Mahendra (International Journal of Research in Interdisciplinary Studies, 2024)
This paper provides a critical review of the ethical issues and methodological advancements in ethnographic research, focusing on the complexities and dilemmas introduced observed in empirical context by different scientific studies. By synthesizing existing literature, the paper examines key ethical concerns such as maintaining ongoing consent and confidentiality, as well as the challenge of balancing researcher engagement with the field, and subjective worldview with objective reality. It also explores the impact of technological advancements and digital tools, including their role in studying online communities and diverse cultural settings. These innovations offer substantial benefits for enhancing ethnographic research but also introduce new ethical dilemmas that require thoughtful consideration. To conclude, this paper highlights the necessity for researchers to integrate these new methodologies while upholding rigorous ethical standards, offering insights into how ethnographic practice can adapt to contemporary challenges while preserving its foundational principles.